Psychological stress and its relationship to skill performance level on the balance beam for first-year students at the College of Physical Education and Sports Sciences, University of Duhok - Abdel-Masih, L.Dr. Raheeq Matta; Al-Hayali, Asst.Prof.Dr. Hadeel Dahi Abdullah (Sulaimani Journal for Humanities, 2026)
The research aims to identify the relationship between the degree of psychological stress and the level of skill performance on the balance beam for second-year female students at the College of Physical Education and Sports Sciences, University of Duhok. The descriptive approach was used using the correlation method due to its suitability for the nature of the research. The research sample consisted of (33) second-year female students at the College of Physical Education and Sports Sciences, University of Duhok. The psychological stress scale prepared by Rana Al-Zawi (1992) was used. To process the data statistically, the arithmetic mean, standard deviation, percentage law, t-test for one sample, and simple correlation coefficient were used through the application of the statistical package (SPSS). It was concluded that psychological stress did not affect the performance of motor skills on the balance beam among second-year female students
Keywords: Psychological stress; a balance issue